YouTube and Rhinoplasty: An Analysis of the Videos Available Online. Issue 4 (December 2017) - Gupta, Amar; Nissan, Michael; Rayess, Hani; Zuliani, Giancarlo F.; Carron, Michael
The objective of this study was to examine YouTube videos related to rhinoplasty created by both physicians and nonphysicians in order to determine the content of the videos, the selected topics of discussion, and other important parameters. A cross-sectional analysis was performed. YouTube videos that resulted when the search term "rhinoplasty" was entered were identified during the first 15 days of October 2014. The search was carried out daily during this time, and the first 20 unchanged videos were included in this analysis. Authorship, length of video, objective, total views, and type of video were recorded. Ten videos (50%) were physician based, 8 were patient based (40%), and 2 (10%) were television programs. Ten videos (50%) were longer than 10 minutes and 8 (40%) had greater than 100 000 views. The majority of videos (85%) aimed to provide didactic information on the rhinoplasty operation or intended to provide a perspective on the operation from an actual patient. Mann-Whitney U tests and Kruskal-Wallis tests were used to compare physician-based Web sites against those with other authorship with threshold of significance < .05 with no significant difference found between the groups. Videos submitted by practicing physicians were inherently different than those submitted by patients. While videos submitted by physicians concentrated primarily on the actual operation, videos submitted by patients were focused mainly on what they experienced during their procedure. The lack of safeguards on the quality or accuracy of videos posted on the popular Web site YouTube may lead to a possibility for misinformation to the consumer. It would likely be prudent for specialty bodies and organizations to submit high-quality videos to provide the best and most up-to-date information possible.